Addressing Marketing Inefficiencies in Hanjeli Agribusiness (A Value Chain Analysis at the Pantastik Cooperative Sumedang) - Fransisca Johana Tania; Ahmad Choibar Tridakusumah; Ernah Ernah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This study aims to analyze the structure of the hanjeli agribusiness value chain, identify opportunities for value addition, evaluate the marketing efficiency of hanjeli products, and develop strategies for the further development of the hanjeli agribusiness at the Pantastik Cooperative. The research was conducted from January to March 2025 using a qualitative descriptive approach and a case study method. Data were collected from 16 informants, comprising five hanjeli farmers, three cooperative managers, three agricultural extension officers, three business partners, and two government representatives. Data analysis involved value chain mapping and marketing margin analysis. Findings indicate that the hanjeli agribusiness is managed integratively from upstream to downstream, involving actors such as farmers, cooperatives, and supporting institutions. The processing stage contributes the highest value addition at 23%, while marketing efficiency remains low at 19%, primarily due to high distribution and promotional costs. Based on these findings, this study outlines several development strategies to address key bottlenecks across the value chain, including upstream coordination, processing improvement, and market access expansion. These strategic insights provide practical entry points for enhancing the sustainability and competitiveness of Hanjeli agribusiness in rural settings.